2011
DOI: 10.5194/hess-15-209-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate change impact on hydrological extremes in two source regions of the Nile River Basin

Abstract: Abstract. The potential impact of climate change was investigated on the hydrological extremes of Nyando River and Lake Tana catchments, which are located in two source regions of the Nile River basin. Climate change scenarios were developed for rainfall and potential evapotranspiration (ETo), considering 17 General Circulation Model (GCM) simulations to better understand the range of possible future change. They were constructed by transferring the extracted climate change signals to the observed series using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 28 publications
(34 reference statements)
4
131
0
Order By: Relevance
“…The land use map (1 km) in this study was obtained from the Land Cover Institute (LCI) (http://landcover.usgs.gov/). Daily meteorological data such as temperature and precipitation were collected from the Ministry of Water Resources and Electricity and other different sources for the period (Beyene et al, 2010;Taye et al, 2011;Enyew et al, 2014;Gebre et al, 2015). The MIROC-ESM and CCSM4 (Jury, 2015) models similarly have been selected (Elshamy et al, 2009;Beyene et al, 2010;Setegn et al, 2011).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The land use map (1 km) in this study was obtained from the Land Cover Institute (LCI) (http://landcover.usgs.gov/). Daily meteorological data such as temperature and precipitation were collected from the Ministry of Water Resources and Electricity and other different sources for the period (Beyene et al, 2010;Taye et al, 2011;Enyew et al, 2014;Gebre et al, 2015). The MIROC-ESM and CCSM4 (Jury, 2015) models similarly have been selected (Elshamy et al, 2009;Beyene et al, 2010;Setegn et al, 2011).…”
Section: Datamentioning
confidence: 99%
“…The climate change in the Upper Blue Nile basin has been addressed by many previous studies using different climate models and techniques (Elshamy et al, 2009;Beyene et al, 2010;Taye et al, 2011;Setegn et al, 2011;Enyew et al, 2014;Gebre et al, 2015). The Dinder River (DR) is one of the largest tributaries of the Blue Nile River and a major water resource in the Dinder National Park (DNP).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is apparent that the changes in hydrological extremes, i.e. floods and droughts, would have more profound and immediate impacts on agriculture, economy, and human health than the seasonal or monthly changes (Arnell 2011;Taye et al 2011). Changes in hydrological extremes are expected to vary between basins.…”
Section: Introductionmentioning
confidence: 99%
“…It is described that hydrological impacts of climate change on the Lake Tana water balance are not well explored [2] [3]. Recently, by applying a perturbation downscaling approach of GCM outputs, [4] investigated the impact of climate change on high rainfall and flow extremes for the Nyando River and Lake Tana catchments in the Upper Blue Nile basin, Ethiopia. The result of their study indicated increases in temperature but did not indicate systematic increases or decreases of rainfall besides changes in inter-annual variability.…”
Section: Introductionmentioning
confidence: 99%